Self-Concept of College Students With ADHD: Discordance Between Self- and Parent-Reports. (February 2013) - Nelson, Jason M.
Objective: To investigate the self-concept of college students with ADHD.Method: College students with ADHD and their parents completed self-report and observer-report measures of self-concept, respectively.Results: Results indicated that college students with ADHD did not report problems with self-concept but their parents did for them. This difference was statistically significant and large in magnitude ( d = .84).Conclusion: Perceptions of the self-concept of college students with ADHD appear to vary by informant source. Hypotheses for the discordance between self- and parent-reports are discussed. Multi-informant assessment is recommended as a way to obtain a more complete clinical picture than reliance on self- or parent-report alone.